Study on Evaluation and Prediction of the Degree of Surface Damage Caused by Coal Mining - Xie, Xiaoshen; Hou, Enke; Long, Tianwen; Feng, Dong; Hou, Pengfei; Wei, Qiming; Li, Yang; Liu, Jiangbin (Frontiers in Earth Science, 2022)
Surface damage caused by coal mining is one of the problems perplexing ecological environment restoration in coal mining area. Accurately evaluating and predicting the degree of surface damage induced by coal seam mining with reasonable and correct indexes are of great significance to the restoration and treatment of ecological environment. In the paper, these methods including the UAV aerial photography and manual measurement were used to investigate the development characteristics of surface damage caused by 2# coal seam mining in Yangchangwan coal mine. The results show that with the change of mining conditions, the characteristics of surface cracks change obviously, which can be adopted to indicate the degree of surface damage. Thus, on the basis of the results of the investigation, the classification standard of surface damage degree was established based on the evaluation indexes including density of crack, drop height of surface crack, crack width, maximum surface subsidence, geological disasters caused by crack and the characteristics of building damage. The evaluation method and process of surface damage degree also was given. Based on ratio of the buried depth to the thickness of coal seam (H/M), ratio of the thickness of overlying bedrock to the thickness of coal seam, thickness of loose layer(Ms), geomorphology, distance to faults and distance to folds, the prediction model of suface damage degree was built on the GIS platform. The weight coefficient of each prediction index was obtained by the Analytic Hierarchy Method (AHP).The surface damage degree map of 2# coal seam in Yangchangwan Coal Mine was divided into four classes: very minor, minor, moderate and serious, which provides a relatively applicable method for the prediction of surface damage degree in Yangchangwan Coal Mine and its adjacent mining areas.